Divalent Ytterbium Iodide Supported by β‐Diketiminato Based Tridentate Ligand: Synthesis, Structure and Small Molecule Activation†. Issue 3 (23rd January 2020) - Liu, Xiaojuan; Xiang, Li; Wang, Chen; Wang, Bingwu; Leng, Xuebing; Chen, Yaofeng
Summary of main observation and conclusion: Divalent ytterbium iodide [LYb( μ ‐I)(THF)]2 (1 ; L = [MeC(NDIPP)CHC(Me)NCH2 CH2 NMe2 ] −, DIPP = 2, 6‐( i Pr)2 C6 H3 ) was synthesized and its reactivity was studied. Complex 1 was synthesized by salt metathesis of YbI2 (THF)2 with the potassium salt of ligand (KL) in high yield. In the reactions with trimethylsilyl azide, azobenzene, sulfur and diphenyl disulfide, complex 1 acts as a 2e reductant. In the reaction with CO2, the central carbon atom of β‐diketiminato backbone in 1 nucleophilically attacks the CO2 molecule to give a divalent ytterbium carboxylate. Abstract : Divalent ytterbium iodide [LYb( μ ‐I)(THF)]2 (1 ; L = [MeC(NDIPP)CHC(Me)NCH2 CH2 NMe2 ] −, DIPP = 2, 6‐( i Pr)2 C6 H3 ) was synthesized. This complex easily undergoes redox reactions with trimethylsilyl azide, azobenzene, sulfur and diphenyl disulfide and nucleophilic reaction with CO2 .